The Relationship between Limb Power with Distance Kick Soar-Far Using The Inner Feet Side in Carlos FC Football Club, Aceh Besar - Muzakir Muzakir; Junaidi Junaidi; Boihaqi Boihaqi (International Conference on Multidisciplinary Research, 2022)
This research is entitled: "The Relationship between Leg Power and Long Distance Kicks Using the Inner Legs at CARLOS FC Aceh Besar Soccer Club 2016". This study aims to determine the relationship between leg power and long-range bounce using the inside of the foot at the CARLOS FC Aceh Besar football club. The sample in this study were 20 athletes from the CARLOS FC Aceh Besar football club. The data collection techniques used in this study were: (1) the leg power test was carried out using a vertical jump test and was measured using a measuring board, (2) long distance kicks were measured using a meter. The research results obtained were that there was a relationship between leg power and long-range bounce using the inside of the foot at the CARLOS FC Aceh Besar football club with a correlation coefficient of 0.85. Keywords: Power Leg, Long Distance Kick